Impact of food grade antioxidants on peanut pods and seeds mycoflora in storage system from Córdoba, Argentina - Passone, Maria Alejandra (2008)
A 5-month (2005) study was conducted in Argentina to determine the effect of food-grade antioxidants (butylated hydroxyanisole [BHA], butylated hydroxytoluene [BHT] and propyl paraben [PP]) alone and in mixtures on fungal spoilage from stored peanuts. Five experimental containers were filled with 200 kg of bulk peanuts. Four of them were treated with BHA (10 mM), BHA-PP mixture (10 + 10 mM) and BHA-PP-BHT mixtures (10 + 5 + 10 mM) and (10 + 10 + 10 mM). Fungal counts from peanuts treated with binary and ternary mixtures were often significantly reduced. A total of 10,997 fungal isolates were identified from the control pod and seed tissues in the six samplings done compared to 5,164, 1,469, 1,217 and 1,228 fungi isolated from silos 2, 3, 4 and 5, respectively. Ninety-eight percent of all fungi isolated were Deuteromycetes and Ascomycetes. Fungal isolation was greater from pod (91.9%) than from seed tissues. The most common fungi identified included Penicillium, Aspergillus, Monascus, Eurotium and Fusarium spp. Isolation frequencies of Penicillium spp. from both peanut tissues treated with antioxidant mixtures were reduced about of 82.5%. Along the storage period, the reduction percentages of Aspergillus spp. counts by antioxidant mixtures were estimated in 74.5%. The fungal genus more sensitive to the antioxidants action was Fusarium spp.